Nivolumab-Induced Development of Pulmonary Sarcoidosis in Renal Cell Carcinoma. (September 2017) - Zhang, Meng; Schembri, Geoffrey
Abstract : Abstract: A 64-year-old woman with metastatic clear cell renal carcinoma who had been on nivolumab immunotherapy for 10 months was referred for a FDG PET scan to monitor disease progress. New bilateral mediastinal and hilar FDG-avid lymphadenopathy was noted. Pathology on subsequent mediastinal nodal biopsy showed well-formed epithelioid granulomas with no evidence of malignancy consistent with sarcoidosis. This case illustrates that pulmonary sarcoidosis can be induced by immunotherapy in the treatment of renal cell carcinoma.